Measuring the New Construct 'Ethics and Norms-Based Work': A Construction from Human Capital Theory with Religious Norms in Indonesia - Hasmin, Hasmin; Nurung, Jumiaty (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
Purpose: This study aims to develop the